DEVELOPMENT OF ECOLOGY IN UZBEKISTAN - R.N.Mo’minova; G’.Mahkamov; S.Sobirjonov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
At present, the issue of protection of nature and the solution of all environmental problems is one of the most important pressing problems after the maintenance of peace on Earth. The article covers the classifications of Ecology, Environmental Protection textbooks and manuals published by scientists of Uzbekistan to educational methodological works, dictionaries.